Analisa UI/UX Sistem Informasi Penjualan Berbasis Mobile Menggunakan Metode Prototype: Analisa UI/UX Sistem Informasi Penjualan Berbasis Mobile Menggunakan Metode Prototype Pada PT. Anugerah Mitra Semesta - Siti Nurbaiti Oktaviani; Chairul Fikri Aziz; Besus Maula Sulthon (KLIK: Kajian Ilmiah Informatika dan Komputer, 2022)
In general, companies have problems that make a job more difficult. Apart from taking a long time, ineffective processing can also have a negative impact on a company. PT. Anugerah Mitra Semesta is a company engaged in PVC trading. The problem that exists in PT. Anugerah Mitra Semesta is the Sales Information System which is still done manually. Thus making the company slower in pursuing sales targets. Therefore, the solution that can help these problems is to conduct an analysis in order to create a good sales program, easy to use and become an illustration for making a sales program for the company. This analysis is used with UI/UX design using the prototype method. The Prototype method is a design display system design process that is created as an example to develop a product as an illustration for the user directly, and the types presented are Wireframe, Mockup and prototypes